Implementation of the juvenile criminal justice standards in the prosecution function (Legal journal - Research in Legal and Social Sciences, 2020)
This  investigation  adresses  the  importance  of  developing  meaningfully  the  criminal jurisdiction specialized in young offenders, to ensure one the pillars of the human  right  of  access  to  justice  for  the  mentioned  population,  in  order  to  assure  the respect and implementation of all the general and specific standards established by  national  and  international  legal  instruments  that  support  due  diligence  in  the  context  of  a  criminal  investigation.  With  this  understanding,  some  of  the  guiding  principles are: the right not to be discriminated against, the equality before the law, the right to be judged by specialized justice workers, the presumption of innocence, the  lawfulness  and  judicial  security,  the  best  interest  of  the  child/adolescent,  the  progressive autonomy and the right to be heard, among others. To make these rights effective, Paraguay needs to continue with the suitability of its home legislation, but based on the enforced International Conventions, as a State Party of the Convention on the Rights of the Child and other international legal instruments related to the Rights of the Child. Furthermore, it is important to adopt mechanisms to assure the full implementation of the juvenile justice standards, by justice workers.
Keywords: juvenile criminal justice; Paradigms; Standards; Principles; access to justice; human rights.